2021
DOI: 10.1097/j.pbj.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auditory or visual stimuli on gait in Parkinsonic patients: a systematic review

Abstract: Background: External stimuli can improve gait performance in Parkinsons Disease (PD): auditory stimuli can increase velocity and visual stimuli may act at step length.Objective: To systematize the scientific evidence about the effects of auditory or visual stimuli on gait in patients with PD.Methods: From January 2016 to December 2018, a systematic literature research was conducted in the PubMed/Medline and Web of Science databases. Study designs considered were randomized controlled trials (RCTs) and observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…Recent studies support the idea that cueing can be an effective component of locomotor therapy for patients with PD and gait disturbance, that auditory cueing is most effective for influencing the temporal parameters of gait only, and that visual cueing has been used to improve the spatial parameters 10,11) and reduce step/stride length variability and asymmetry 11) . Focusing on the effects of cueing on FOG in patients with PD, Lee et al compared the effects of visual and auditory cues on patients with PD who were experiencing FOG, and found that visual cues reduced FOG increased stride length and gait speed, and improved lower extremity joint movements during walking 12) .…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies support the idea that cueing can be an effective component of locomotor therapy for patients with PD and gait disturbance, that auditory cueing is most effective for influencing the temporal parameters of gait only, and that visual cueing has been used to improve the spatial parameters 10,11) and reduce step/stride length variability and asymmetry 11) . Focusing on the effects of cueing on FOG in patients with PD, Lee et al compared the effects of visual and auditory cues on patients with PD who were experiencing FOG, and found that visual cues reduced FOG increased stride length and gait speed, and improved lower extremity joint movements during walking 12) .…”
Section: Introductionmentioning
confidence: 89%
“…Although auditory stimuli and music are used for the treatment of Parkinson-related gait disorders and postural instability 190 191 192 , the importance of auditory rehabilitation for Parkinson patients is not discussed in therapy studies.…”
Section: Hearing Disorders In Frequent Neurodegnerative Diseases In H...mentioning
confidence: 99%
“…Obwohl auditorische Reize und Musik zur Behandlung von Parkinson-bedingten Gangstörungen und posturaler Instabilität eingesetzt werden 190 191 192 wird in Therapiestudien die Bedeutung der Hörrehabilitation für Parkinsonpatienten nicht diskutiert.…”
Section: 31 Schwerhörigkeit Und Parkinsonunclassified
“…Mais de 85% das pessoas com DP desenvolvem dificuldades de locomoção dentro de 3 anos após o diagnóstico, devido à alteração dos sintomas motores [4]. Os distúrbios da marcha são considerados os sintomas motores mais incapacitantes da DP, levando a um declínio substancial na mobilidade e independência, uma alta taxa de quedas e uma redução na qualidade de vida [5].…”
Section: Introductionunclassified
“…Estudos confirmam que os pacientes com DP precoce e avançada apresentam comprometimento da marcha e que o padrão específico da marcha anormal é caracterizado por redução da velocidade da marcha [5][6][7], redução do comprimento do passo [5], comprimento da passada reduzida [6][7][8] e diminuição da rotação do tronco combinada com uma cadência aumentada [5,6]. Devido a essas deficiências, existe uma grande tendência de pacientes com DP terem uma redução da capacidade de andar, o que determina a redução da função motora [8].…”
Section: Introductionunclassified